A Theory Approach towards Tradable Rail Freight Option - Jingwei Guo; Lutian Li; Ji Zhang; Qi Shen; Zhongqi Xie; Qinglin Li (Discrete Dynamics in Nature and Society)
For railway freight pricing, this paper proposes a new tradable rail freight option (RFO). A multiphase trigeminal tree pricing model is established to analyze the optimal pricing decision of RFO. The main parameters of the model are identified theoretically through nonparametric Ito stochastic approach. The paper expands the theory of railway freight pricing. The aim of this paper is to construct the railway freight option theory to help railway transportation enterprise cope with fierce competition and challenge from other modes of transportation in China. The most significant feature of this method is its simplicity in analyzing the optimal pricing decision using only the algebraic category and Ito’s lemma.